Color Development Characteristic and Kinetic Modeling of Maillard Reaction in Membrane-Clarified Sugarcane Juice During Vacuum Evaporation Process - Meiyi Han; Hongkui Zhao; Zhihua Liu; Jing Liu; Xi Liu; Fangxue Hang; Kai Li; Caifeng Xie (Foods)
This study systematically investigated the evolution of color values and the reaction kinetics of the Maillard reaction in membrane-clarified sugarcane juice during the vacuum evaporation process, providing a theoretical basis for pigment regulation in white sugar production. Content changes in the reactants (sucrose, glucose, fructose, and free amino acids), the precursors of melanoidins including 3-deoxyglucosone, 5-hydroxymethylfurfural, glyoxal, methylglyoxal, carboxymethyl lysine, and melanoidin, were monitored during the thermal processing of membrane-clarified sugarcane juice (MCSJ), and the reaction mechanism was investigated via kinetic modeling. The zero-level, first-level, and second-level kinetic models could represent the change in L* and b*, and the zero-level kinetic model best fit the change in a* and ΔE*. The multi-response kinetics revealed that the main pathway of melanoidins in MCSJ model systems was that glucose and fructose were mutually isomerized into 1,2-enediol to generate 3-DG and then degraded to produce 5-HMF. Subsequently, 5-HMF further reacted to produce melanoidins.